Cezanne - Cezanne, Paul 1839-1906; Cahn, Isabelle; Feilchenfeldt, Walter; Loyrette, Henri; Rishel, Joseph J. (New York Harry N. Abrams in assocation with Philadelphia Museum of Art, 1996)
"This monumental volume reveals a man whose desire for perfection was seconded only by an exceptional capacity for work. Cezanne's entire existence was consecrated to painting, and he left an indelible impression on all painters who came after him. He was fully conscious of his role as a prophet who, as the critic Thadee Natanson wrote in 1894, had effected an absolute overthrow of the art of painting." Provided by publisher
Includes bibliographical references (pages 580-589) and index.
Keywords: Cézanne, Paul, 1839-1906 -- Exhibitions